LEGITIMATE VIOLENCE IN ILLEGITIMATE TIMES: DIO'S THEORIES OF LEGITIMACY. - Beek, A. L. (Akroterion, 2019)
Comparing legitimacy in the three different contexts of literary leisteia, Late Republican civil war actors, and contemporary Severan emperors reveals Dio to be consistent when discussing legitimate violence. In all three, Dio presents establishing legitimacy as a primary factor in attaining power. As the required skills to achieve power differed from those for ruling, the resulting ruler could be disastrous. Through employing the 'noble bandit' topos, Dio questions the emperors' suitability, comparing them to bandits. Overall, Dio interprets Late Republican history differently from his sources for Republican history. In his view, future statesmen cannot rely upon the mos maiorum.